Vocabulary Exercises and Reading Comprehension: Evidence from Iranian ESP Learners at the Undergraduate Level - Noori, Narges; Rahimi, Ramin; Mashhadi Heydar, Davood (Assessment and Practice in Educational Sciences, 2024)
The purpose of the present study was to examine the relationship between vocabulary exercises and reading comprehension among Iranian ESP learners. The research method employed was a quasi-experimental pre-test–post-test design. The research population consisted of 40 Iranian ESP undergraduate learners of accounting who were selected through the administration of the Oxford Placement Test (OPT) and participated in the experiment of this study. They were divided into experimental and comparison groups and underwent a reading comprehension pre-test. Subsequently, the experimental group received five sessions of vocabulary exercises. Finally, a post-test was administered to both groups. Data were analyzed using the independent samples t-test between post-tests, and a paired samples t-test was employed to demonstrate the possible improvement of the groups. The results indicated superior performance of the experimental group, which obtained higher scores in the reading comprehension post-test after five sessions. The analysis of the learners’ reading comprehension performance, which was independently compared between the pre-test and post-test of the experimental and control groups, revealed that participants with a degree of knowledge in vocabulary exercises reflected more successful performance in their ESP reading comprehension test. This may suggest that teaching vocabulary exercises can assist them in improving their reading comprehension activities.